Japan : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that the GDP growth in Japan slowed unexpectedly in the second quarter of 2004, after several quarters of above-trend growth. For the full year, GDP rose by 2.6 percent, well below expectations. A significant part of the shortfall reflected a shift to a chain-weighted methodology-growth on the old methodology was 3.6 percent. Pressure on labor markets from job shedding is slowly abating. Progress in corporate restructuring continues. Cash flow and profits remain buoyant; bankruptcies have fallen to a 10-year low and leverage continues to decline.